PRAKTIK BAIK POJOK BACA KELAS III SDN 16 SUNGAI PINYUH - -, Khotimah; Yunika Afryaningsih; Salman Al Farisi (Universitas Tanjungpura, 2026)
This study aims to describe the best practices of reading corners in the third-grade classroom at SDN 16 Sungai Pinyuh and analyze their impact on students' reading interest and literacy skills. The main focus of the research includes aspects of facilities, book collections, teacher roles, and the evaluation and sustainability of the reading corner. The method employed is qualitative descriptive, with data collected through observations and interviews with teachers and students. The findings indicate that the reading corner serves as an effective tool for enhancing students' reading interest. Engaging facilities, such as easily accessible bookshelves and supportive decorations, create a conducive learning environment. The diverse collection of books, including both fiction and non-fiction appropriate for the age and interests of the students, encourages children to read more actively. The active role of teachers as facilitators and motivators is crucial in supporting students' reading activities, including guiding them in selecting appropriate books. Furthermore, regular maintenance and periodic evaluation of the reading corner ensure the sustainability of the literacy program in the school. This research is expected to contribute positively to the development of a reading culture among students and serve as a reference for other schools in managing reading corners.